PROLONGED ACTIVATION OF THE BAROREFLEX DECREASES ARTERIAL PRESSURE EVEN DURING CHRONIC ADRENERGIC BLOCKADE - Lohmeier, Thomas E. (2009)
Previous studies suggest that prolonged electrical activation of the baroreflex may reduce arterial pressure more than chronic blockade of α(1)-and β(1,2)-adrenergic receptors. To determine whether central inhibition of sympathetic outflow has appreciable effects to chronically reduce arterial pressure by actions distinct from well established mechanisms, we hypothesized that chronic baroreflex activation would lower arterial pressure substantially even during complete α(1)-and β(1,2)-adrenergic receptor blockade. This hypothesis was tested in 6 dogs during adrenergic blockade (18 days) with and without electrical activation of the carotid baroreflex (7 days). During chronic adrenergic blockade alone, there was a sustained decrease in mean arterial pressure of 21±2 mm Hg (control = 95±4 mm Hg) and nearly a 3-fold increase in plasma norepinephrine concentration (control = 138±6pg/mL), likely due to baroreceptor unloading. In comparison, during adrenergic blockade + prolonged baroreflex activation, plasma norepinephrine concentration decreased to control levels and mean arterial pressure fell an additional 10±1 mm Hg. Because of differences in plasma norepinephrine concentration, we also tested the acute blood pressure lowering effects of MK-467, a peripherally acting α(2)-antagonist. After administration of MK-467, there was a significantly greater fall in arterial pressure during adrenergic blockade (15±3 mm Hg) than during adrenergic blockade + prolonged baroreflex activation (7±3 mm Hg). These findings suggest that reflex-induced increases in sympathetic activity attenuate reductions in arterial pressure during chronic adrenergic blockade and that inhibition of central sympathetic outflow by prolonged baroreflex activation lowers arterial pressure further by previously undefined mechanisms, possibly by diminishing attendant activation of postjunctional α(2)-adrenergic receptors.